Hardware architecture design of face recognition system based on FPGA - Mondol, Raktim Kumar; Khan, Muhammadimran; Mahbubul, Hye, A. K.; Hassan, Asif S. (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 2nd IEEE International Conference on Innovations in Information, Embedded and Communication Systems, ICIIECS 2015; Karpagam College of EngineeringCoimbatore; India; 19 March 2015 through 20 March 2015 [© 2015 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/ICIIECS.2015.7193228